DIATESIS DALAM BAHASA MANDAILING AIR BANGIS KABUPATEN PASAMAN BARAT - Handoko, Fredy Handoko; ', Charlina; ', Auzar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This study entitled voice in Mandailaing language Regional Air Bangis West Pasaman. The purpose of this study was to describe the structure of the active diathesis, describing the structure of the passive voice, describing the structure of reflexive voice, and describe the structure of reciprocal voice. The method used in this research is descriptive method with qualitative research. This research data is the local unit of language Mandailaing Air Bangis West Pasaman containing diathesis. Results of the study found the overall type of voice of 4 types voice studied in the language Mandailaing Air Bangis area West Pasaman with each voice has a different argument types. The number of types of arguments that affect each type of voice include, the active voice has 6 types of arguments, the passive voice has 6 types of arguments, reflexive voice has 1 type of argument, and reciprocal voice have 2 types of arguments. Key Words: Voice in Mandailing Language Air Bangis.